Non-extractable polyphenols of green tea and their antioxidant, anti-α-glucosidase capacity, and release during in vitro digestion. (March 2018) - Yan, Shuaishuai; Shao, Hongjun; Zhou, Zhihao; Wang, Qi; Zhao, Luhua; Yang, Xingbin
Highlights: The polyphenolic profile of green tea NEPP was established for the first time. The NEPP showed considerable in vitro antioxidant activities. The NEPP exhibited noncompetitive inhibition against α-glucosidase. The NEPP can be partly released by stimulated in vitro digestion. Abstract: The extractable and non-extractable polyphenols (EPP and NEPP) of green tea were characterized. The results showed that the total polyphenolic content of NEPP was 4 times lower than that of EPP, and polyphenolic profiles of NEPP and EPP were also remarkably different, both qualitatively and quantitatively. Furthermore, the antioxidant activity of NEPP, determined by DPPH, ABTS and FRAP assays, was lower compared with EPP, but higher than vitamin C. Meanwhile, NEPP also exhibited α-glucosidase inhibitory effect (IC50 1.96 ± 0.21 µg/mL) in a noncompetitive manner. Additionally, an in vitro digestion of the green tea residues after EPP extraction led to the release of NEPP, in which gallocatechin, epigallocatechin, catechin, and epicatechin, along with caffeine, were the most abundant compounds. The results of this study indicated that NEPP of green tea are untapped natural sources of antioxidants and α-glucosidase inhibitors.